A rewriting decision procedure for Dijkstra-Scholten’s syllogistic logic with complements - Rocha, Camilo; Meseguer, José (Revista Colombiana de Computación, 2007)
We present an equational decision procedure a la Dijkstra & Scholten for the 'Syllogistic Logic with Complements'. Keywords: Syllogistic Logic with Complements, Decision Procedure, Equational Logic, Rewriting Logic, Maude.